Effect of Literary Text Reception in Individualized and Responsible Classroom Teaching - Dragić, Želimir Ž.; Ilić, Mile Đ. (Collection of Papers of the Faculty of Philosophy in Priština, 2018)
Reception of literary text in teaching is a new methodical concept that was defined and explicated in this paper for the first time. Transferable theoretical foundations of literary text reception in teaching for younger school age students were developed through synthesis of key assumptions of the reception theory, the theory of innovative-developmental teaching and findings of tangential pedagogical-psychological and didactic-methodical research. Operationalization of these foundations enabled their incorporation in the starting points, structures, characteristics and microteaching plans for literary text perception in interactive teaching with different levels of complexity (IN RNS – as a modality of individualized teaching system) in responsible teaching (RN). Through selection and interpretation of thematically relevant theoretical achievements, we have tried to establish new microteaching plans and exercises for reception of literary texts in innovative-developmental classroom teaching. In a three-month long experiment, the students of fifth grade of primary school received artistic-literary text in the aforesaid innovative-developmental classroom teaching systems. On average, statistically significantly higher results were achieved on the final rather than on the initial measurement in knowledge of literary-theoretical concepts, judgement in social situations and in identification and evaluation of elementary types of personality.
Keywords: reception of literary text in teaching; reception theory; developmental teaching theory; teaching with different levels of complexity; responsible teaching; knowledge of literary-theoretical concepts; judgement in social situations; identification and evaluation of personality types